APPLICATION OF ADDING ALBUMIN POWDER FROM WHITE CHICKEN EGG TO ACCELERATE WOUND HEALING IN DOMESTIC CATS - Wining Astini; Syahida Eviliana; Nida Ul Millah (Fakultas Kedokteran Hewan Universitas Udayana, 2025)
Stray cats frequently present with varous dermatological abnormalities and are susceptible to vulnus morsum (bite wounds) from fights with other animals. In this case report discusses a male domestic cat, aged >1 year and weighing 2 kg, presented to the cilinic with foul-smelling wounds exhibiting signs of suppuration and necrosis on all four limbs, face, and jaw area due to a systemic infection. This study aims to evaluate the effect of supplementary egg white albumin powder on accelerating the wound healing process. The provided therapy included Limoxin spray, long-acting amoxicillin injection, Glucortin injection, and oral supplementation of Bio trans factor®, a combination of albumin powder from egg white extract, vitamin A, vitamin E, egg yolk extract, depp-sea fish oil, and chana fish extract-administered at 2.5 g twice daily for 7 days. Observation results indicated that the combination therapy was effective in promoting new skin and fur growth and significantly reducing wound size by day. It concluded that supplementation with egg white albumin powder and supportive nutrients may serve as an effective adjuvant therapy for accelerating the healing of complex wounds in cats. Suggestions are needed for similar research with more complete examinations such as hematological examinations to see the effect of albumin administration on the hematological profile of cats or tissue examination using histological anatomical analysis.